Health Communications in Traditional Chinese Medicine Cardiology - Al-Shura, Anika Niambi; Al-Shura, Anika Niambi (Elsevier Science, 2014)
Health Communication in Traditional Chinese Medicine Cardiology presents an overview of health communications including history, cardiovascular prevalence and role of Chinese medicine, interpersonal communications between practitioners and patients, and explores methods in epidemiology to follow symptom, diagnostic, treatment and follow-up patterns in the clinic. The book integrates the role of Chinese medicine in public health efforts, classifying the identity of the practitioner and the needs of certain patient types who require this kind of matching for better health and research methods to help sharpen the focus for specializing practitioners.Identifies the rationale for specializing in cardiovascular Chinese medicine as an important part of current public health needsPrepares practitioners to adjust their skills, knowledge, attitudes, and behaviors, and to guide patients to do likewise for better health outcomesPrepares the practitioner to sit for the Niambi Wellness Health Communications 1 final online exam